Bilateral Inflammatory Aural Polyps: A Manifestation of Samter's Triad. (21st December 2009) - Brobst, Robert; Suss, Nichole; Joe, Stephanie; Redleaf, Saadia
Abstract : We report an unusual case of bilateral inflammatory aural polyps in a patient with Samter's triad. This 52-year-old patient had a history of chronic rhinosinusitis with sinonasal polyps, asthma, and aspirin sensitivity, with progressive right-sided hearing loss, otorrhea, and aural fullness. She was found to have bilateral aural polyps, with the larger obstructing lesion on the right. A computed tomography supported these findings and revealed bilateral opacification of the middle ear cleft and mastoid air cells. An initial right tympanomastoidectomy was performed with the specimen histologically resembling a typical sinonasal polyp. We speculate that this patient's middle ear polyposis is secondary to the inflammatory changes of Samter's triad. This has not been described previously in the literature.